ANALISIS PERENCANAAN ULANG STRUKTUR PONDASI PADA PROYEK COFFEE SHOP DI KAWASAN PUSAT INFORMASI GEOPARK KALDERA TOBA DESA HUTARAJA KABUPATEN SAMOSIR - Kurnia Rahmadiansyah; Diana Suita Harahap (Jurnal Teknik Sipil, 2022)
The coffee shop in Hutaraja village is one of the supporting facilities in the Toba Caldera Geopark area which aims to increase tourist attraction in the area along with the construction of the Toba Lake area to become one of Indonesia's mainstay ecotourism destinations. The number of floors in this coffee shop project is 1 floor using a foot foundation with a depth of 0.60m. By considering the initial design of the foundation which also uses the foot foundation.The foundation is a part of the structure that functions as a support for the building to distribute the load on it (upper structure) to a layer of soil that has a sufficiently strong soil bearing capacity. The foundation must not decrease beyond the permit limit, therefore careful planning is needed. From the results of the analysis with sondir test and calculations using the Meyerhoff method, the bearing capacity of the soil on the P1 foundation is obtained = 172.89 kN/m2, the maximum soil stress that occurs at the base of the foundation = 149.537 kN/m2, two-way shear strength on the foundation = 869.677 kN by fulfilling the requirements for the shear force that occurs is = 214.435kN. with the foundation using D16-200mm reinforcement. So that the foot foundation is used with a cross-sectional width of 1.50 x 1.50m, this is greater than the initial design of the planned foundation with a size of 0.80 x 0.80m, due to the displacement of the planning location and different soil types.